Preparation and use of a Grafted Silica with Imidazole Groups for Cadmium Sorption and Subsequent Voltammetric Detection of Ascorbic Acid - Serantoni da Silveira, Tayla Fernanda [UNESP]; Fernandes, Daniela Silvestrini [UNESP]; Barbosa, Priscila Fernanda P. [UNESP]; do Carmo, Devaney Ribeiro [UNESP] (Springer Nature, 2018)
Inorganic-organic hybrid materials, such as silica gel functionalized with an organic group, offer many applications in several areas of interest. The adsorptive properties provided by these materials due to the presence of active donor atoms such as O, N and S of grafted organic groups, suggests their application in metal ions adsorption as well as in the preparation of electrochemical sensors for substances of interest. In this work a hybrid material formed by interaction of a 3-chloropropyl silica gel modified with imidazole was characterized by techniques such as infrared spectroscopy, 29Si and 13C nuclear magnetic resonance and analysis of surface area and porosity. Adsorption studies were carried out for cadmium (II) in different media, and the quantity of adsorbed metal increased according the following order of solvents: water < ethanol 42% < ethanol 99%. After cadmium ions adsorption, the material was reacted with potassium hexacyanoferrate forming the material CdHSGI that was incorporated into a graphite paste electrode. Electrochemical studies were conducted with cyclic voltammetry. The cyclic voltammogram showed one redox couple with average potential E=0.25 V (vs Ag/AgCl, NaNO 3 1.0 mol L−1; v = 20 mVs−1), attributed to the Fe2+(CN)6/ Fe3+(CN)6 process. The modified electrode allowed the electrocatalytic ascorbic acid determination. Through voltammograms it was possible to observe a linear range from 1.0 × 10−4 mol L−1 to 9.0 × 10−4 mol L−1 (R = 0.996) for the ascorbic acid determination with a detection limit of 7.9 × 10−5 mol L−1 with a relative standard deviation of 3% (n = 3) and amperometric sensitivity of 11.1 mA/ mol L−1.
Keywords: Adsorption; Ascorbic acid; Graphite paste electrode; Imidazole; Silica gel; Voltammetry